IMPLEMENTASI DIFFERENTIAL COST DAN OPPORTUNITY COST DALAM PENGAMBILAN KEPUTUSAN MEMBUAT SENDIRI ATAU MEMBELI - Wahyuliningtyas, Sekar; Ratih, Nur Rahmanti; Kusummaningarti , Miladiah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
Determining a decision to be taken by Tulungagung Ababiel Convection, it must be supported by sharp considerations. Making the right decision will result in an advantage for the company. One of the methods used in decision making is the differential cost method in making decisions to choose an option to increase profits. Making decisions using the differential method, it has something to do with opportunity costs where these costs aim to make choices and determine the decisions that must be taken and sacrifice other choices. By knowing this relationship, Ababiel Tulungagung Convection party can estimate how the implementation of differential costs and opportunity costs is in making decisions to make yourself or buy from outside so you can find out the right decisions for the company.The data analysis technique used in this study is a quantitative descriptive analysis technique. Data obtained from interviews and documentation. From the results of the analysis carried out, the research results show production costs which include raw material costs, labor costs, and factory overhead costs. After knowing the costs incurred, a comparison is made of the costs incurred by the company when producing itself with the cost of buying from suppliers. The company also uses opportunity costs to find out the opportunities the company gets if the company buys from outside and rents out the building it owns.